Synthesis, structural and pharmacological exploration of 2-(3, 5-dimethyl-1H-pyrazol-1-yl)-acetophenone oximes and their silver complexes. (1st February 2021) - Sharma, Tulika; Kumar, Rakesh; Chandra Sahoo, Subash; Sindhu, Jayant; Singh, Joginder; Singh, Bijender; Kumar Mehta, Surinder; Umar, Ahmad; Singh Saini, Tej; Kumar, Vinod; Kataria, Ramesh
Graphical abstract: Hirshfeld surfaces, antibacterial and DNA photo-cleavage activity of aceto-phenone oximes and their silver complexes. Highlights: Pyrazole-oxime based silver complexes have been synthesized and characterized. Silver complexes (4g–4l) explained on the basis of X-ray crystallographic analysis. Ligand and their complexes have been screened for antibacterial and DNA photo-cleavage activity. The intermolecular interactions and electrostatic properties have been extensively explored. Abstract: Some new compounds, 2-(3, 5-dimethyl-1 H -pyrazol-1-yl)-4-substituted acetophenone oximes [4a–4f; here, 4-substituent =  H (a ), Br (b ), Me (c ), Cl(d ), NO2 (e ), F (f )] were synthesized by the reaction of 2-(3, 5-dimethyl-1 H -pyrazol-1-yl)-1-arylethanones with hydroxylamine hydrochloride. These compounds were characterized by analyzing their IR, 1 H, 13 C NMR and mass spectral data. Compounds 4a–4f were further converted into their silver complexes (4g–4l ) and chemical structures of which were established on the basis of their X-ray crystallographic data. The antibacterial and DNA photocleavage activity studies were carried out for all the synthesized compounds 4a–4l, and it has been found that compound 4l displayed an excellent level of antibacterial and DNA photocleavage activity. Among the series, Ag-complexes (4g–4l) displayed excellent antibacterial activity against four bacterial strains using Ciprofloxacin as a standard drug. In DNA photocleavage study, it has been observed that compounds 4a, 4e, 4f degraded both forms of DNA, whereas their Ag-complexes degraded DNA completely even at a very low concentration. The intermolecular interactions present in 4g and 4h were described by decomposing Hirshfeld surfaces into 2D fingerprint plots. It was observed that non-polar interactions contribute dominantly in overall intermolecular interactions exit in crystals of both the compounds.